Robocasting of dense zirconia parts using commercial yttria-stabilized zirconia granules and ultrafine particles. Paste preparation, printing, mechanical properties. Issue 2 (15th January 2022) - Mohammadi, M.; Becker, G.; Diener, S.; Tulliani, J.-M.; Katsikis, N.; Palmero, P.
Abstract: In this work, a commercial 3 mol% yttrium oxide partially stabilized zirconia spray-dried granules were used as such, and after intensive milling, for the production of dense samples by robocasting technique. The aim was to evaluate the suitability of using spray-dried granules instead of submicron particles in robocasting of ceramic parts. To this aim, robocasting pastes were produced from the as-received granules as well as from nanometric particles obtained from an effective ball milling of the granules. The formulation of the pastes was optimized in order to achieve optimal printability. The drying conditions were optimized as well, and the control of temperature and humidity either in the printing and drying chambers allowed to eliminate any warping issue. After sintering at 1450 °C, the monolithic dense parts were characterized by ultra-fine and highly sintered microstructures, with the highest density achieved by the sample produced from granules. This material not only did not show the typical defects of granules-derived ceramics but was also characterized by fewer and smaller defects than the sample produced by the fine particles. It seemed that the presence of large granules, and thus large intergranular space, favored the debinding process and limited the formation of the typical processing flaws. The ball-on-three balls test was used for the evaluation of the mechanical properties of the dense samples. Biaxial flexural strength values in the range from ∼100 to 500 MPa (with an average value of 255 ± 93 MPa) were determined for the samples made from granules while these values ranged from ∼100 to 300 MPa (with an average strength of 198 ± 52 MPa) for the samples prepared from the milled particles. In spite of low, these values are in line with literature data, obtained on 3 mol% Y2 O3 –ZrO2 samples fabricated by the robocasting technique, and suitable to demonstrate the feasibility to use as-received granules as feeding material for robocasting parts.